Pengembangan Media Gamifikasi Berbantuan Crossword Puzzle untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Informatika Kelas VIII SMP - Salsa Elza Monika; Zelhendri Zen; Meldi Ade Kurnia Yusri; Khairul Alfahani (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aimed to develop a web-based HTML5 gamification learning media in the form of a digital crossword puzzle on the topic of Digital Literacy that meets valid, practical, and effective qualifications. This study was a Research and Development (R&D) project using the 4D development model (Define, Design, Develop, and Disseminate). Data collection instruments included expert validation sheets (material and media), practicality questionnaires (student responses), and effectiveness scales (user engagement questionnaires). Data were analyzed using both quantitative and qualitative methods. The results showed that: (1) The material validity test by educational practitioners achieved a score of 92% ("Very Valid"). Media validity by Media Expert I scored 98.94% ("Very Valid") and Media Expert II scored 95.8% ("Very Valid"). (2) The practicality test based on grade VIII student response questionnaires reached an average percentage of 88.8% ("Very Practical"), driven by the flexibility of cross-platform accessibility without requiring application installation. (3) The effectiveness test based on the user engagement scale achieved an average percentage of 87.1% ("Very Effective"). The integration of real-time feedback and time-challenge elements successfully stimulated students' cognitive focus, intrinsic motivation, and critical thinking skills. Based on these findings, it is concluded that this crossword puzzle gamification media is feasible, practical, and highly effective for utilization as an innovative learning tool in junior high school Informatics